A Bio-Social Review to Mitigate the Punishment of Unwanted Acts - Alimardani, Armin; Ardekani, Ali M.; Astany, Leila R. (International Journal of Criminology and Sociology, 2014)
Commitment of crime and exhibition of antisocial behavior have been considered as negative acts from early times of human civilization. Recent scientific advances have identified contributions of biological and sociological (environmental factors) factors in forming a maladaptive behavior. Generally, it is accepted by many scholars that punishing a wrongdoer, who has committed a crime owing to genetic predispositions and environmental elements, is not effective and forms of treatments should be replaced to avoid repeating a crime. Moreover, by identifying genetic deficiencies in an individual, an antisocial behavior could be potentially predicted and prevented before it comes to pass. On a whole, genetic and environmental factors, sometimes solely and some other times collaboratively, lead a person to act against society norms. In summary, this body of literature offers examples that explain factors which contribute to committing crimes and approaches which inhibit antisocial behavior. With regard to these aims, we suggest that punishment of criminals who are predisposed genetically in the same manner as other delinquencies is not justifiable and a reduction of punishment should be applied to such individuals. Moreover, by eliminating each of negative elements which contribute to antisocial behavior or crime, we can be more certain that the offender will not repeat antisocial acts after being released.